2017
DOI: 10.1177/2054358117695792
|View full text |Cite
|
Sign up to set email alerts
|

First Canadian Case Report of Kidney Transplantation From an HIV-Positive Donor to an HIV-Positive Recipient

Abstract: Rationale:Kidney transplantation has become standard of care for carefully selected patients living with human immunodeficiency virus (HIV) and end-stage renal disease (ESRD) in the highly active antiretroviral therapy (HAART) era. American and European prospective cohort studies have reported similar patient and graft survival compared with HIV-negative kidney transplant recipients. Despite an increased rate of acute rejection, partially due to drug interactions, HIV immunovirologic parameter generally remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
3
8
0
Order By: Relevance
“…Drawing on favourable experience in South Africa we have undertaken the first UK kidney transplants between HIV-infected individuals with excellent outcomes after 2 years of follow-up. Our results and others’ [ 5 ] demonstrate that kidney transplantation between carefully selected HIV-infected donors and recipients is a safe and effective treatment option with the potential to expand the organ donor pool for HIV-positive patients with end-stage kidney disease.…”
Section: Discussionsupporting
confidence: 68%
“…Drawing on favourable experience in South Africa we have undertaken the first UK kidney transplants between HIV-infected individuals with excellent outcomes after 2 years of follow-up. Our results and others’ [ 5 ] demonstrate that kidney transplantation between carefully selected HIV-infected donors and recipients is a safe and effective treatment option with the potential to expand the organ donor pool for HIV-positive patients with end-stage kidney disease.…”
Section: Discussionsupporting
confidence: 68%
“…In 2015, Ambaragassi et al reported the first case of kidney transplantation from an HIV‐positive donor to an HIV‐positive recipient in Canada, showing an excellent outcome after 7 months of follow‐up, with good graft function and adequate control of HIV replication in the absence of opportunistic infections …”
Section: Discussionmentioning
confidence: 99%
“…These positive results, together with the chronic scarcity of available organs, have encouraged the idea of using organs from HIV‐positive donors for select HIV‐positive recipients, and the initial experiences seem to suggest promising short‐term outcomes …”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are no reports of kidney transplants from living donors who are hepatitis C virus (HCV) or human immunodeficiency virus (HIV) infected, only deceased donor cases. 77,78 Individuals infected with HCV have a high chance of cure following therapy with newer direct-acting antiviral therapy. 79,80 Certain Canadian transplant centers with access to these newer therapies are already accepting kidneys from deceased donors who are HCV positive to be transplanted into recipients who are HCV negative.…”
Section: Review Processmentioning
confidence: 99%